¡ALIMENTAR EL CONOCIMIENTO!: LA IMPORTANCIA DE UNA BUENA NUTRICIÓN EN LA PRIMERA INFANCIA PARA EL ADECUADO DESARROLLO COGNITIVO, EMOCIONAL Y FÍSICO (Memorias Sifored - Encuentros Educación UAN, 2023)
The current research addresses the critical issue of malnutrition in early childhood and its direct impact on development and learning. Using a methodology based on bibliographic review and content analysis, studies and literature from the last 10 years were examined. The findings highlight that malnutrition in the early stages of life leads to significant delays in brain, cognitive, and emotional development, resulting in deficiencies in academic performance and socialization. The conclusions emphasize the urgent need for early interventions, educational programs, and public health policies that holistically address malnutrition and its implications in the educational field.
Keywords: Health education; Malnutrition; Early childhood; Cognitive, emotional and physical development; Academic performance